COVID-19 and fear processing - Rathod, Pravin R.; Rathod, Santhi. P.; Kandwal, Rishabh R.; Panicker, Geo J. (International Journal of Research in Medical Sciences, 2023)
The world faces a global crisis that encompasses health, financial, and psychological aspects as a result of the coronavirus disease. While the health crisis is significant, it is important to recognize that the human and social crises that have emerged are equally impactful. These crises have resulted in various negative outcomes, such as social rejection, economic disparity, unemployment, and mental distress. Fear is a significant psychological barrier that can impede recovery from any disease process, and thus, it plays a critical role in determining the mortality and morbidity of any given disease. The COVID-19 pandemic has generated a pervasive fear of infection that has further exacerbated the situation. This study explored the mechanisms by which humans may have elicited conditional fear, using the COVID-19 pandemic as a specific case study. Our goal was to examine the process of fear in humans by exploring our knowledge of neuroanatomy and the systemic response regulated by the autonomic nervous system.